Evaluation of an iPhone Otoscope in a Neurotrauma Clinic and as an Adjunct to Neurosurgical Education - Sahyouni, Ronald (Insights Neurosurg, 2016)
INTRODUCTION: CellScope(®), an iPhone-enabled otoscope, was introduced into the neurotrauma clinic at an American College of Surgeons certified Level I trauma center. CellScope is an innovative tool that digitally improves optical clarity of the tympanic membrane, providing the acquisition of HIPPA compliant images. We compared the CellScope to the traditional otoscope in teaching medical students, neurosurgery physician assistants, and neurosurgery residents. In addition, the utility of this device in a neurotrauma clinic was specifically examined because of the high frequency of otologic symptoms after head trauma. METHOD: CellScope examination of the tympanic membranes was introduced as a standard/routine part of the exam of neurotrauma patients. We retrospectively reviewed the clinic charts of the NeuroTrauma patients during a three-month time period to determine if their otologic symptoms correlated with any CellScope visualized abnormalities. Medical students, P.A.s, residents, and attendings were surveyed before and after using CellScope to assess their comfort and skill in completing an otological exam, as well as their opinion on the utility of CellScope in their medical training. RESULTS: 18 medical professionals were surveyed before and after the use of CellScope. Surveys were graded on a 1-5 scale and indicated a greater preference for the CellScope (4.7/5.0) versus the otoscope (3.16/5.0). Similarly, there was a preference for the CellScope for medical education (4.7/5.0 versus 2.78/5.0). Finally, surveys showed a greater preference for CellScope in identifying abnormal pathology. The overall score showed a 49% increased preference for CellScope over the traditional otoscope. Six previously undiagnosed abnormalities of the tympanic membrane were identified in a total of 27 neurotrauma patients using CellScope. CONCLUSION: The visualization of the tympanic membrane is an important part of the physical examination of the neurotrauma patient. Smartphone-enabled medical instruments like CellScope may facilitate and remove barriers to routine implementation of this part of the physical examination.